2020
DOI: 10.1002/adfm.202005069
|View full text |Cite
|
Sign up to set email alerts
|

Printable Organic‐Inorganic Nanoscale Multilayer Gate Dielectrics for Thin‐Film Transistors Enabled by a Polymeric Organic Interlayer

Abstract: Here, a new approach to the layer-by-layer solution-processed fabrication of organic/inorganic hybrid self-assembled nanodielectrics (SANDs) is reported and it is demonstrated that these ultrathin gate dielectric films can be printed. The organic SAND component, named P-PAE, consists of polarizable π-electron phosphonic acid-based units bound to a polymeric backbone. Thus, the new polymeric SAND (PSAND) can be fabricated either by spin-coating or blade-coating in air, by alternating P-PAE, a capping reagent la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…1−4 In addition to the results presented here, the potential use of solution-processed SANDs in manufacturing is further strengthened by the recent development of printed SANDs. 16 The well-known sensitivity of a-IGZO to atmospheric effects is known to contribute to device instability and is a major attraction of top-gate devices. 37,48,66 Numerous studies have reported improved environmental stability of top-gate a-IGZO TFTs using a variety of dielectric materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1−4 In addition to the results presented here, the potential use of solution-processed SANDs in manufacturing is further strengthened by the recent development of printed SANDs. 16 The well-known sensitivity of a-IGZO to atmospheric effects is known to contribute to device instability and is a major attraction of top-gate devices. 37,48,66 Numerous studies have reported improved environmental stability of top-gate a-IGZO TFTs using a variety of dielectric materials.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Furthermore, the advantages are limited not only to the broad array of compatible unconventional semiconductors but also in the tailorability of the SAND structure itself in regard to both the inorganic 6−8 and organic components. 15,16 Note that IGZO is currently the most important manufactured metal oxide semiconductor material, and sputtered IGZO TFTs have been implemented in many commercial devices. 3 In previous studies, we demonstrated combustion synthesis as a route to high-quality amorphous IGZO (a-IGZO) films from precursor solutions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Three-dimensional (3D) printing can readily fabricate complex 3D structures, which is hard to achieve by traditional processing methods [1,2]. Therefore, 3D printing has wide applications in various fields, such as electronics, biomedical engineering, energy industry, and aerospace [3][4][5][6][7][8][9][10][11][12][13][14]. There are many types of 3D printing technologies such as digital light processing (DLP), selective laser sintering (SLS), stereolithography (SLA), fused deposition modeling (FDM), and direct ink writing (DIW) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Ceramic materials that have a high dielectric constant are widely used as high- k ceramic fillers. These ceramic materials include barium titanate (BT; BaTiO 3 ), titanium dioxide (TiO 2 ), hafnium dioxide (HfO 2 ), zirconium dioxide (ZrO 2 ), copper calcium titanate (CCTO), and BaSrTiO 3 nanofibers . Among these ceramic materials, ZrO 2 is the most extensively studied dielectric and is widely considered to be an excellent candidate because of its relatively high dielectric constant, low leakage current, good thermal stability, large band gap (5–7 eV), and high k (25) .…”
Section: Introductionmentioning
confidence: 99%